Molecular binding interaction of angiotensin converting enzyme and 1-galloyl glucose, the major compound in Syzygium polyanthum leaves - Tuan Anuar, Tuan Ashraf Faiz; Ismail, Azlini; Omar, Muhammad Nor; Mohamed Suffian, Izzat Fahimuddin; Abdul Hamid, Azzmer Azzar (Kulliyyah of Science, International Islamic University Malaysia, 2021)
Syzgium polyanthum leaves are traditionally used for treating hypertension. Recently, the plant leaves extract has been demonstrated to exhibit significant angiotensin-converting enzyme (ACE) inhibition activity, and this has further consolidated the evidence for its antihypertensive effect. Previously, 1-galloyl glucose has been suggested as its possible bioactive compound, however, there is no specific study yet on its interaction with ACE enzyme specifically through molecular docking. Therefore, this study aims to investigate the molecular interaction between 1-galloyl glucose (CID 124375) and the ACE protein (PDB: 1086). The standard ACE inhibitor drug captopril (CID 44093) was used as a comparison. Autodock 4 (California, USA) was utilized to prepare the protein and ligand; meanwhile, the docking simulation was conducted in Autodock Vina (California, USA). Molecular docking analysis showed that 1-galloyl-glucose has lower binding energy (-7.7 kcal/mol) with the ACE, as compared to the captopril (-5.6 kcal/mol). Both compounds showed specific interaction mainly towards histidine group, with 1-galloyl glucose specifically bind towards several residues of aspartic acid group. 1-galloyl glucose was shown to have more binding residues than captopril, hence contributed to the binding energy. All these residues were shown to have hydrogen bonds with distance lower than 3.5 A ; indicative of good interaction between 1-galloyl-glucose and the ACE. In conclusion, 1-galloyl glucose has better binding affinity towards ACE enzyme than the standard drug, captopril. This finding further supported the potential of 1-galloyl glucose as one of the possible bioactive compounds responsible for ACE inhibition by S. polyanthum.